Development and characterization of Kyllinga Nemoralis soap: a preliminary study - Rosni, Nur Syafiqah; Alan Shahrin, Razween Balqis; Abdul Aziz, Rosmawati; Hasyim, Saiyidah Nafisah (2024)
The objective of this preliminary investigation was to create and identify a soap that was made with extract from Kyllinga nemoralis (K.nemoralis), with an emphasis on its physicochemical properties, performance, and safety for use. The soap was manufactured by employing a conventional saponification process that included K.nemoralis extract. The soap that resulted was subjected to a variety of characterization experiments. Organoleptic evaluations were conducted on the color, odor, and texture. Washability was evaluated by observing the simplicity of rinsing, and the pH was measured using a pH meter. The detergent sample's moisture content was ascertained by drying it and calculating the weight difference. In order to assess the foaming properties, foam retention duration and foam height were measured. Volunteers were assessed for skin irritability by administering the soap solution to a small area of their skin and observing for any adverse reactions. The soap had a solid and firm texture, a grassy odour, and a dark green colour. The soap's pH was determined to be 8, which suggests that it is mildly alkaline and suitable for cleansing. The detergent was easily washable and did not leave any residue after rinsing. The bar was robust and durable because of its 10.11 % moisture content. The foam retention time was 150 minutes, and the foam height was 64 mm, indicating exceptional foaming properties. It is crucial to note that the detergent did not induce any skin irritation, which implies that it is suitable for general use. The soap that has been developed with K.nemoralis extract exhibits promising qualities, such as outstanding foaming performance, balanced moisture content, effective washability, and appealing organoleptic properties. The product is appropriate for daily use due to its mild alkalinity and absence of skin irritation. It is advised that additional research be conducted to investigate the long-term effects on skin health and the comparative efficacy of commercial soaps. This investigation validates the potential of K.nemoralis extract as a valuable component in natural detergent formulations.s.